FROM THE EDITOR’S DESK - Dr. Fatema Jawad (Journal of the Pakistan Medical Association, 2023)
Another turbulent year is over. We enter 2024 with a Prayer for our country and its inhabitants. May the Almighty Allah have Blessings for all of us. May we make progress in all fields of life. May the standard of education improve in our country and thus better doctors, lawyers, teachers and people in all other fields form the galaxy of the population. Many young medical graduates have left the country for better prospects abroad. Others are trying their luck within the country with many not being able to find a training ground due to lesser slots and too many applicants. All medical students are wanting to publish articles, cases or even Letters. Unfortunately the mentors are scarce with little time and ability to teach research and its writing. Desperation leads to employment of unethical means. In the journal office we witness many irregularities while performing desk reviews. This leads to back and forth communication with the authors and having the feeling of not being able to convince them. Ethics seems to have become an old fashioned word. In the past year, we have encountered cases of plagiarism, undeserved authorship, inadequate Institution Review Board’s certificates, forged signatures and many more. WHY are our people getting involved in these unethical acts? It is disappointing and shameful. We are trying to teach all about research and publication ethics, hoping for a new horizon. So Life and Work go on. No journal can have success without a good and efficient staff. I am grateful and appreciative of the efforts put in by our office workers, Mr. Abdul Majid, the office manager along with the efficient team comprising of Mr. Adil, Faizan, Munib, Nasir and Ramzan. The core members of the editorial board include, Drs. Anwar Siddiqui, Sina Aziz and Mubin. We have been lately joined by Dr.Hasnain to help out with the desk work. They are all the decision makers and have important responsibilities. Presently there are four students helping out with all types of office work along with it they are learning the responsibilities of the editorial staff and how to perform the technical review of case reports.. We have good news to share. JPMA is now registered with DOAJ!! This will give a greater visibility to the publication. I also take this opportunity to thank all our peer reviewers who are the heart of the journal.The reviewers are spread out in the entire country and abroad. Some have been with us for over twenty years. No journal can function without good peer reviewers. We are fortunate to have many new ones aspiring to learn. I also express my gratitude to all the authors who have confidence in JPMA and submit their articles for consideration of publication. It may take a bit long, but it is fair work. May the standards of research improve in our country which will provide classic articles and attract readership from the entire world. My NEW YEAR Greetings and Good Wishes are extended to all related to JPMA. May our country have peace and prosperity which will eventually reflect on every aspect of life including our worthy publications. May the Almighty show us the correct path to lead a pure and righteous life. May our medical students, doctors and their mentors have the will to carry out and publish ethical research. May the year 2024 bring Peace, Righteousness and Joy for all.